Complimenting and Teaching Compliments in the Iranian EFL Instructional Context - Saadati, Soodeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This was a multi-method exploratory-interpretive study involving a cross-sectional survey (DCT administration) as well as a subsequent pragmatic instruction motivated by the necessity to promote the EFL learners’ overall pragmatic development at one of the largest English Language Institutes in Iran. The study involved 30 Persian native speakers, 30 British English native speakers, 120 Iranian EFL learners across different English language proficiency levels, and 10 Iranian EFL learners enrolled in an oral communication class where pragmatic teaching was implemented. The present study collected comprehensive qualitative data comprising the participants’ DCT responses, classroom discussion transcriptions, completed mini-research observation forms, Iranian EFL learners’ reflections reports, and it employed quantitative as well as qualitative interpretive analytical procedures. The study findings revealed some pragma-linguistic as well as socio-pragmatic similarities and differences in realization of compliments and related responses between the Persian and British English native speakers. Further, the results demonstrated the Iranian EFL learners’ developing knowledge of complimenting in the target language which still required improvement, especially in terms of the L2 socio-pragmatic conventions. Finally, the triangulation of the data collected by the teacher-researcher showed that the pragmatic instruction of compliments enhanced socialization opportunities for the Iranian learners’ pragmatic development in the target language. Keywords: Iranian EFL learners, cross-sectional survey, pragmatic instruction, compliment, compliment response, pragmatic development,DCT, socialization.

ÖZ: İran'daki en büyük İngilizce Dil Enstitülerinden birinde İngilizce’yi yabancı dil olarak öğrenen (EFL) öğrencilerin edimbilim eğitimini takiben onların genel edimbilimsel gelişimini artırmak amacı ile başlatılan (ve DCT yönetiminin kullanımını içeren) bu kesitsel araştırma, edimbilimsel öğretimi içeren çok yönlü keşfedici-yorumlayıcı bir çalışmadır. Bu araştırma farklı İngilizce dil yeterlilik seviyelerinde olan 120 İranlı, anadili Farsça olan 30 ve anadili İngilizce olan 30 katılımcıyi ve edimbilimsel öğretimin uygulandığı sözlü iletişim sınıfına kayıtlı 10 İranlı EFL öğrenciyi içermektedir. Kapsamlı nitel verilerin toplandığı bu çalışmada araştırmaya katılan öğrencilerin DCT yanıtlarını, sınıf tartışma yazılımlarını, küçük ölçekli araştırma gözlem notlarını, İranlı EFL öğrencilerin düşüncelerini paylaştıkları görüşleri analiz etmek için nicel ve nitel yorumlayıcı analitik prosedürler kullanılmıştır. Çalışma bulguları Farsça ve İngilizce ana dilinde yapılan iltifatlar ve bu iltifatlara verilen yanıtlar bağlamında bu iki dil arasında pragma-dilbilim ve sosyo-pragmatik benzerlikler ve farklılıklar bulunduğunu ortaya koymuştur. Çalışma bulguları ayrıca İranlı EFL öğrencilerin hedef dili İngilizce’de geliştirmeye çalıştıkları iltifat bilgilerini özellikle sosyo-pragmatik bağlamda hala daha iyileştirmeye ihtiyaçları olduğunu göstermiştir. Özet olarak bu çalışmada öğretmen-araştırmacı tarafından üçgenleme yöntemi kullanılarak toplanan emik verilerin analiz sonuçları, edimbilimsel iltifat eğitiminin İranlı öğrencilerin sosyalleşme fırsatlarını artırdığını ve onların hedef dili İngilizce’deki edimbilimsel gelişimlerini artırdığını ortaya koymuştur. Anahtar Kelimeler: anadili Farsça olan EFL öğrencileri; kesitsel araştırma; edimbilimsel öğretim; iltifat; iltifat yanıtı; edimbilimsel gelişim; sosyalleşme.
Doctor of Philosophy in English Language Teaching (ELT). Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2019. Supervisor: Prof. Dr. Gülşen Musayeva Vefalı.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching; Iranian EFL learners; cross-sectional survey; pragmatic instruction; compliment; compliment response; pragmatic development; DCT; socialization